Long-term care facilities for older people and the COVID-19 pandemic: epidemiological data and preventive measures - Tatiana Teixeira Barral de Lacerda; Marcella Guimarães Assis; Vitoria Nunes Silva; Luiza Gabriele Dutra Duarte; Ana Paula Rodrigues Gonçalves; Poliana Fialho de Carvalho; Natália de Cássia Horta; Marina Celly Martins Ribeiro de Souza; Leani Souza Máximo Pereira (Brazilian Society of Geriatrics and Gerontology, 2023)
Objectives: The COVID-19 pandemic has challenged society, especially residents of long-term care facilities (LTCF). This study investigated rates of infection, hospitalization, and death due to COVID-19 among LTCF residents and staff in Minas Gerais, Brazil and identified strategies to control the spread of the disease. Methods: This cross-sectional study collected data from 164 LTCF (6017 older adults). The owners or managers were invited to answer an electronic questionnaire. The questionnaire included 55 items, divided into 3 sections. Results: Of the participating LTCF, 48.7%, 39.6%, and 32.3% reported COVID-19 infections, hospitalizations, and deaths, respectively, among residents, while 68.9%, 7.3%, and 1.2% reported COVID-19 infections, hospitalizations, and deaths, respectively, among staff. Preventive measures were identified and classified as organizational, infrastructural, hygiene items/personal protective equipment, and staff training. Conclusion: The strategies used in the daily routines of LTCF during the pandemic were classified. The challenges experienced in Brazilian facilities were similar to those observed worldwide. The results highlight the importance of continuity and the need to improve protective measures for LTCF residents, especially in low- and middle-income countries.